El baile de los 41 (2020): remediando miradas en torno a la homosexualidad en busca de la generación de un canon conmemorativo (Monográfico) - Charlois Allende, Adrien José (2022)
In 2019, the 41st LGBTTTI Pride March was held in Mexico City under the slogan “41: To be is to resist”. Which nestled in the famous raid of 1901 the possibility of being named as an act of resistance in the community. It established on that date the moment when Mexico could break the silence and hatred of traditionalism, the possibility of verbalizing identity. In 2021, Netflix released on its VOD platform the film “El baile de los 41” (2020), directed by David Pablos. The screenwriter, Monika Revilla, proposed that her decision to retake the episode was founded on the need to give seriousness to an act she considered a “coming out of the closet of homosexuality in Mexican society”. Both elements highlight the importance of the famous dance as a histo-identity. In this text we propose to analyze the 2020 film through the idea of the construction of memory canons by the effect of remediation. It takes as a metaphor of analysis the work of Carlos Monsiváis regarding the event, to evidence the way in which a film product of the VOD platform recovers different remediations to reiterate the idea of a mythical event for the LGBTTQ+ community, from which the struggles for their rights can be understood in terms of present values that are explained in a specific past.